Eﬀect of weight around ankle on decreasing hip ﬂexion excursion during gait in children with diplegia - Ibrahim, Nahla M.; Elsayed Abbass, Mai (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Children with diplegia have considerably larger hip ﬂexion excursion during the gait cycle than normal develop-ing children. There have been few studies that look at the eﬀect of ankle loading on gait in children with hemiparesis, but none that look at the eﬀect of ankle loading on hip ﬂexion angles during gait in children with diplegia, to our knowledge. The purpose of the study is to evaluate the eﬀect of using a weight around the ankle on the degree of hip ﬂexion excursion in children with diplegia.Methods. Fifty children with spastic diplegia were assigned into 2 groups at random (A, B). Both groups received the same prescribed exercise program with gait training for group A and gait training while using a weight around the ankle for group B. Treatment was conducted for 1 hour 3 sessions/week for 3 successive months. Two-dimensional (2D) gait analysis was used to evaluate hip excursion throughout the gait cycle before and after the 3 months of therapy.Results. Mixed design MANOVA was used to study the eﬀect within each group and between the 2 groups. A comparison of both groups after treatment demonstrated a signiﬁcant decrease in right and left hip ﬂexion excursion in the initial swing, mid-swing, terminal swing, initial contact, mid-stance, and pre-swing (p > 0.01). There was no signiﬁcant diﬀerence in loading response between groups after treatment (p = 0.3).Conclusions. Using weight around the ankle during gait helped to decrease the degree of excessive hip ﬂexion excursion during gait in children with diplegia.
Keywords: cerebral palsy; gait analysis; ankle weight loading